Prevalence of metabolic syndrome in patients with psoriasis: a cross-sectional study in a tertiary care hospital of North India - Aggarwal, Kamal; Sharma, Shruti (International Journal of Research in Dermatology, 2019)
Background: Psoriasis is a chronic inflammatory disorder of skin, which has been recently linked to metabolic syndrome (MetS) by studies worldwide. Paucity of Indian data in this regard led us to conduct the present study, which aimed to identify the prevalence of metabolic syndrome (and its components) in patients with psoriasis and to determine its association with disease severity and duration. Methods: This was a hospital-based cross-sectional study conducted over 50 clinically diagnosed patients of chronic plaque psoriasis and 50 age- and sex-matched control subjects. Metabolic syndrome was diagnosed by the South Asian Modified National Cholesterol Education Program Adult Treatment Panel III criteria (SAM-NCEP criteria). Data was analyzed using SPSS (version 17, SPSS Inc. Chicago, Illinois, USA). Descriptive statistics (mean, standard deviation, percentage), student’s t-test, and chi-square test were used. Results: Metabolic syndrome was more prevalent in psoriasis patients than controls but the difference was not significant statistically (30% vs 16%, p=0.0979). Although psoriasis patients had higher prevalence of hypertrigly-ceridemia, hyperglycemia, hypertension and central obesity than controls, but the difference was statistically insignificant. The prevalence of low high-density lipoprotein (HDL) cholesterol was significantly higher in cases compared to controls (40% vs 18%, OR 3.0370, p=0.0159). Conclusions: Metabolic syndrome and dyslipidemia are common in psoriasis patients, which signify the need for routine screening of metabolic syndrome in those patients.